2012
DOI: 10.1186/1471-213x-12-27
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged FGF signaling is necessary for lung and liver induction in Xenopus

Abstract: BackgroundFGF signaling plays numerous roles during organogenesis of the embryonic gut tube. Mouse explant studies suggest that different thresholds of FGF signaling from the cardiogenic mesoderm induce lung, liver, and pancreas lineages from the ventral foregut progenitor cells. The mechanisms that regulate FGF dose in vivo are unknown. Here we use Xenopus embryos to examine the hypothesis that a prolonged duration of FGF signaling from the mesoderm is required to induce foregut organs.ResultsWe show that bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 61 publications
4
26
0
1
Order By: Relevance
“…FGFs have been shown to be required for the initiation of hepatic development in several divergent species (Jung et al 1999;Chen et al 2003;Zhang et al 2004;Shin et al 2011;Shifley et al 2012). Based on such studies, most protocols used to generate hepatocyte-like cells from hiPSCs include the addition of FGF1 or FGF2, commonly along with BMP4, to induce hepatic specification of the endoderm (Cai et al 2007;Agarwal et al 2008;Hay et al 2008;Basma et al 2009;Song et al 2009;Si-Tayeb et al 2010b;Sullivan et al 2010).…”
Section: Fgfr Signaling Is Required For Specification Of Hepatic Progmentioning
confidence: 99%
See 1 more Smart Citation
“…FGFs have been shown to be required for the initiation of hepatic development in several divergent species (Jung et al 1999;Chen et al 2003;Zhang et al 2004;Shin et al 2011;Shifley et al 2012). Based on such studies, most protocols used to generate hepatocyte-like cells from hiPSCs include the addition of FGF1 or FGF2, commonly along with BMP4, to induce hepatic specification of the endoderm (Cai et al 2007;Agarwal et al 2008;Hay et al 2008;Basma et al 2009;Song et al 2009;Si-Tayeb et al 2010b;Sullivan et al 2010).…”
Section: Fgfr Signaling Is Required For Specification Of Hepatic Progmentioning
confidence: 99%
“…Subsequent studies have shown that FGF acts in a concentration-dependent manner, with relatively low concentrations inducing hepatic differentiation and higher concentrations inducing lung development (Serls et al 2005). Since the original discovery in mouse embryos, several reports have demonstrated that FGFs play integral roles in regulating hepatic cell fate in evolutionarily distinct species, including Xenopus, chicks, and zebrafish (Jung et al 1999;Chen et al 2003;Zhang et al 2004;Shin et al 2011;Shifley et al 2012).…”
mentioning
confidence: 99%
“…Unique among aquatic model systems, Xenopus embryos rapidly develop lungs in the first few days of embryogenesis, which at the molecular and histological level are similar to early mouse lungs [60••]. Recent studies have revealed that key signaling pathways implicated in mammalian lung development such as Wnt, FGF and BMP, are conserved in Xenopus lung development [6064]. Using small molecule inhibitors and dominant negative FGFR1 constructs two studies showed that FGF signaling was required for specification of lung tissue, but not thyroid [62, 64].…”
Section: Lung and Thyroid Developmentmentioning
confidence: 99%
“…Recent studies have revealed that key signaling pathways implicated in mammalian lung development such as Wnt, FGF and BMP, are conserved in Xenopus lung development [6064]. Using small molecule inhibitors and dominant negative FGFR1 constructs two studies showed that FGF signaling was required for specification of lung tissue, but not thyroid [62, 64]. Shifley et al also showed that both MEK and PI3K pathways downstream of FGF are essential for lung development [64].…”
Section: Lung and Thyroid Developmentmentioning
confidence: 99%
See 1 more Smart Citation